MAINTENANCE OF THE ROVER SITTER POLYMORPHISM AND THE EFFECT OF MALE-MALE COMPETITION ON MATING SUCCESS IN FRUIT FLIES - Mentlik, Joseph (My University, 2016)
The fruit fly, Drosophila melanogaster is an exceptional model species for understanding both proximate and ultimate causes of variation in behaviour. Here, we have examined two behaviors: foraging and mating. We discuss these research projects in turn. Almost 40 years ago, the classic foraging behaviour polymorphism rover/sitter was first discovered. Recently, evidence has suggested that the polymorphism is maintained by negative frequency-dependent selection at the larval stage. In two separate experiments we failed to replicate negative frequency-dependence in the survival of rover and sitter larvae. However, we empirically demonstrated differences in burrowing behaviour between the rover and sitter morphs which may be a possible mechanism causing the negative frequency-dependent relationship between the morphs. Future replication of negative frequency-dependence is necessary if we are to understand the maintenance of this polymorphism in nature. We examined mating behaviour from the perspective of two mechanisms of sexual selection: female choice and male-male competition. The study of sexual selection requires careful isolation of these mechanisms. Owing to difficulties in experimental design, studies have yet to properly separate and quantify the individual effects of female choice and male-male competition in fruit flies. Here, we designed a novel arena to assess true female choice. We then used this arena to test the effect of male courtship interference on mating outcomes. However, due to an unforeseen amount of male harassment of females in the arena, we withhold any strong conclusions about the effect of male-male interference behaviour. We also attempt to demonstrate the potential for sexual selection on traits associated with interference behaviour in males.
ROVER/SITTER POLYMORPHISM & SEXUAL SELECTION IN FRUIT FLIES
Keywords: Animal behaviour; Drosophila; Rover/Sitter; Courtship Interference